Exploring Eighth Grade Students’ Anxiety in Learning English at SMPN 2 Bolo - Wildaniah, Ririn; Khatimah, Khusnul; Suciwati, Ika (International Journal of Language Teaching and Education, 2026)
Foreign Language Anxiety (FLA) is one of the psychological factors that may influence students’ performance in learning English as a Foreign Language (EFL). Although anxiety is commonly associated with students who have low language proficiency, it can also be experienced by students with relatively good English ability. From a psycholinguistic perspective, anxiety may interfere with cognitive processes involved in language learning, such as attention, memory, and language production. Therefore, this study aimed to explore the types of foreign language anxiety and the factors contributing to anxiety among eighth-grade students with relatively good English proficiency at SMPN 2 Bolo. This study employed a descriptive qualitative design with a psycholinguistic approach. Four participants were selected through purposive sampling based on predetermined criteria, including high academic achievement, relatively better English proficiency, teacher recommendation, and observable indications of anxiety during classroom interaction, particularly speaking activities. Data were collected through classroom observation and semi-structured interviews. The findings revealed that the participants experienced three types of foreign language anxiety, namely communication apprehension, fear of negative evaluation, and test anxiety. Furthermore, the factors contributing to students’ anxiety included internal factors such as lack of confidence, fear of making mistakes, limited vocabulary, and pronunciation difficulties, as well as external factors such as peer judgment and classroom atmosphere. These findings indicate that foreign language anxiety may occur even among students with relatively good English proficiency and can influence their participation during English classroom interaction and speaking activities.